THE INFLUENCE OF EDUCATION AND TRAINING PROGRAMS ON EMPLOYEES CAREER PATH AT PT. PELINDO (PERSERO) REGIONAL 4 MAKASSAR - A. Zahratul Hayati; Zainal Ruma; Uhud Darmawan Natsir; Agung Widhi Kurniawan; Tenri Sayu Puspitaningsih Dipoatmodjo (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2023)
Education and training programs play a crucial role in enhancing employee performance and contributing to organizational success. These programs facilitate the acquisition of new knowledge, industry best practices, and the development of relevant skills. The purpose of this research is to examine the influence of education and training programs on employee career paths at PT. Pelindo (Persero) Regional 4 Makassar. The study population consists of 100 permanent employees at PT. Pelindo (Persero) Regional 4 Makassar, and a cluster sampling technique was used to select a sample of 50 employees. The data was processed using SPSS 26. The research findings indicate a positive influence between the Education and Training Program variable (X) and the Employee Career Path variable (Y). This relationship is represented by the simple regression equation Y = 5.744 + 1.038, and it is supported by a significant t-statistic value of 7.719, which surpasses the t-table value of 2.011, with a significance value of 0.000 < 0.05. The R Square value of 0.554 demonstrates that the education and training program variables contributed to 55.4% of the variance in employee career paths, while the remaining 44.6% was influenced by other unexamined variables. In conclusion, the Education and Training Program has a positive and significant effect on the Employee Career Path at PT. Pelindo (Persero) Regional 4 Makassar. It is crucial for organizations to invest in comprehensive education and training initiatives to foster employee growth and advancement in their careers.